RELIGIÃO E IDENTIDADE: UM ESTUDO SOBRE NEGROS METODISTAS DA REGIÃO METROPOLITANA DE SÃO PAULO - Branchini, Diná da Silva (2008)
This study deals with the relational dynamics of religious and ethnic-racial identities with regard to black persons on Methodist Churches in the Metropolitan Region of São Paulo. The empirical points of reference are Methodist Churches in: Suzano, Itaquaquecetuba Monte Belo, and Central Santo Andre. It analyses the sociocultural construction of religious identities, circumscribed by material, economic and political contingencies of the society in which the research subjects are inserted. It proposes that collective black identity is a mixture of associations, on the one hand negative due to segregationist socioeconomic conditions linked to the institutionalized racism in society and in religious spaces; on the other hand, positively, because of the enriching cultural influences of Brazilian culture, beyond that marked by resistance, developed by black movements. The research demonstrates the role of the Methodist institution that imposes white middle class cultural patterns and control over black manifestations of identity.(AU)